Description of Patient Satisfaction Level with Therapeutic Communication of Nurses in Work Phase - Aeni, Qurrotul; Anggraeni, Rina; Nurwijayanti, Andriyani Mustika (GLOBAL HEALTH SCIENCE GROUP, 2023)
Communication is a very special and important process in relationships. Communication is more important in the nursing profession because interpersonal communication is the starting point of mutual understanding between nurses and patients. because communication is a basic need between nurses and patients, it can be categorized as face-to-face communication between nurses and patients, nurse support, patient support. meet patient needs. The aim of this research is to determine the level of patient satisfaction with nurses' therapeutic communication during the work phase at RSI Muhammadiyah Kendal. The research method used is descriptive quantitative. The sample used in this research was 50 respondents. The research technique used was purposive sampling with a cross sectional approach, to make data collection easier, the tool used was a therapeutic communication questionnaire. Analyze univariate data to obtain the frequency distribution of each variable. The results of research on respondent satisfaction levels show that respondents who choose the satisfaction level of